Proenkephalin-A as a Biomarker for Type 2 Diabetes in Women with Thyroid Disorders - Hassoun, Maryam A.; Abass, Eiman A.A. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: The thyroid is a vital endocrine gland that regulates growth, metabolism, and development. Thyroid dysfunction (TD) and diabetes mellitus (DM) are two prevalent endocrine disorders with overlapping pathophysiological features.Objective: To investigate the potential role of proenkephalin-A (PENK-A) as a diagnostic and predictive biomarker for type 2 diabetes in women with thyroid dysfunction.Methods: A total of 130 women aged 25–55 years were enrolled in the study, including 100 patients with thyroid disorders and 30 healthy controls. The study was conducted from December 2024 to April 2025 at Al-Kindy Center for Endocrinology and Diabetes in Baghdad. Participants were categorized into four subgroups based on the presence or absence of hypothyroidism, hyperthyroidism, and DM. Serum levels of PENK-A, TSH, T3, T4, and HbA1c were measured using different principles of the ELISA technique, while (FBG) Fasting Blood Glucose was determined by the enzymatic colorimetric method using a glucose kit from Randox. To express the data, the mean ±SD was used.Results: PENK-A levels were significantly elevated in patients with both thyroid dysfunction and type 2 diabetes compared to non-diabetic patients and controls. PENK-A demonstrated high diagnostic performance in distinguishing hypothyroidism and hyperthyroidism patients with DM from those without DM, achieving an outstanding AUC of 0.942 and 0.813, respectively. Conclusions: Proenkephalin-A may serve as a sensitive and specific biomarker for predicting and monitoring type 2 diabetes in patients with thyroid disorders.